Advanced colorectal cancer resulting in acute bowel obstruction during pregnancy; a case report. (June 2016) - Ossendorp, Rikkert R.; Silvis, Rob; van der Bij, Gerben J.
Abstract: Introduction: Abdominal pain is frequently found in the pregnant population; however life-threatening pathology such as colorectal cancer does occur rarely. As such, intestinal obstructions are usually attributed to pregnancy-related issues. We present the case of a young woman with an acute bowel obstruction caused by advanced colorectal carcinoma. Presentation of Case: A 34-year old pregnant woman was referred to our emergency department with complaints of severe upper abdominal pain. Initial investigations did not show abdominal pathology and conservative treatment for obstipation was commenced. However, complaints persisted and a near blowout of the colon was diagnosed, prompting a caesarean section and diagnostic laparotomy. An obstructing tumour was found and a left-sided hemi-colectomy was performed. Unfortunately, skeletal, lymphatic and additional hepatogenic metastasis were discovered during chemotherapy and treatment was discontinued. Discussion and conclusion: The mainstay of abdominal complaints during pregnancy can be attributed to normal physiological alterations associated with gravidity. Nonetheless serious pathology should be considered, especially when conservative treatment fails. On this note, diagnostic imaging during pregnancy should be used promptly upon suspicion of serious abdominal pathology. Highlights: Abdominal pain during gravidity is a commonly seen in the emergency room. Even though the incidence is low, it may still be a sign of serious abdominal pathology. Additional imaging is required when diagnosing acute abdominal pain during pregnancy. Suspicion of serious abdominal pathology should arise when no progress is seen during conservative treatment. If the diagnosis is made and the gestational age is sufficient, surgery should not be delayed.